2005
DOI: 10.1523/jneurosci.3861-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Developmental Speeding in AMPA-EPSC Decay Time at the Calyx of Held

Abstract: The time course of synaptic conductance is important in temporal precision of information processing in the neuronal network. The AMPA receptor (AMPAR)-mediated EPSCs at the calyx of Held become faster in decay time as animals mature. To clarify how desensitization and deactivation of AMPARs contribute to developmental speeding of EPSCs, we compared the decay time of quantal EPSCs (qEPSCs) with the deactivation and desensitization times of AMPAR currents induced in excised patches by fast glutamate application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
117
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 54 publications
(88 reference statements)
12
117
1
Order By: Relevance
“…This modification reduced the time constant of desensitization during prolonged application of 10 mM glutamate to 1.9 ms (from 4.0 ms) in simulation (data not shown), which was similar to the experimentally measured value at calyces (Geiger et al, 1995;Koike-Tani et al, 2005). With this modified scheme, we repeated simulation as shown in Figure 7A-C. We found that the rise time decreased as the simulated mEPSC amplitude increased, which was almost identical to the results shown in Figure 7A-C (data not shown).…”
Section: Methodssupporting
confidence: 84%
See 2 more Smart Citations
“…This modification reduced the time constant of desensitization during prolonged application of 10 mM glutamate to 1.9 ms (from 4.0 ms) in simulation (data not shown), which was similar to the experimentally measured value at calyces (Geiger et al, 1995;Koike-Tani et al, 2005). With this modified scheme, we repeated simulation as shown in Figure 7A-C. We found that the rise time decreased as the simulated mEPSC amplitude increased, which was almost identical to the results shown in Figure 7A-C (data not shown).…”
Section: Methodssupporting
confidence: 84%
“…For the mean mEPSC measured with the series resistance compensation, the 10 -90% rise time was 0.21 Ϯ 0.01 ms (n ϭ 8 synapses, 2015 mEPSCs), the 20 -80% decay time was 1.61 Ϯ 0.30 (n ϭ 8 synapses), and the experimentally estimated peak number of AMPA receptors being activated by release of a vesicle is ϳ22 (Sahara and Takahashi, 2001). Furthermore, the time constants of AMPA receptor desensitization and deactivation are ϳ1-3 and ϳ1-1.5 ms, respectively, in the postsynaptic neurons of the calyx-type synapse at 7-to 11-d-old rats (Geiger et al, 1995;Koike-Tani et al, 2005). These time constants are similar to those (desensitization, 4.9 ms; deactivation, 1.1 ms) (data not shown) obtained by simulation using the AMPA receptor reaction scheme of Hausser and Roth (1997).…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…In excised patches, time constants for AMPAR deactivation are close to the fast time constant for AMPAR desensitization, and both are similar to the mEPSC decay (Koike-Tani et al, 2005). If AMPAR desensitization would significantly shape the decay of AP-evoked EPSCs (Trussell and Fischbach, 1989), our deconvolution analysis would underestimate the duration of the release transient.…”
Section: Discussionmentioning
confidence: 72%
“…AMPARs composed of the GluR2, -3 and -4 flop splice variants show faster desensitization than those containing flip variants (Mosbacher et al, 1994;Geiger et al, 1995;Koike et al, 2000;Koike-Tani et al, 2005). Therefore, we considered whether the altered mEPSC time course in 11 aa mutant cells could arise from a larger contribution of flip isoforms.…”
Section: Sybii Action Governs the Time Course Of Cleft Glutamatementioning
confidence: 99%